Dampak Liberalisasi Perdagangan terhadap Pertumbuhan Industri Manufaktur: Studi pada Hubungan Trade Openness dan Laju Pertumbuhan PDB Industri Manufaktur - Alamsyah Alamsyah; Muhammad Syafri (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the effect of trade openness on the growth of the manufacturing industry in Indonesia. The research uses a quantitative approach with simple linear regression analysis methods. The data used are secondary time series data sourced from the Central Statistics Agency (BPS) and the World Bank. The independent variable (X) is measured through the trade openness ratio, while the dependent variable (Y) is measured through the growth rate of the manufacturing sector's GDP. Data analysis is performed using SPSS software with stages of classical assumption testing and hypothesis testing. The results show that trade openness has a positive and significant effect on the growth of the manufacturing industry, with a regression coefficient of 1.791 and a significance level of 0.001 (< 0.05). The coefficient of determination (R²) value of 0.554 indicates that 55.4% of the variation in manufacturing industry growth can be explained by the trade openness variable, while the rest is influenced by other factors outside the model. These findings support the Structural Change theory which states that trade openness can be a catalyst for economic transformation towards more productive sectors. However, its effectiveness still depends on the readiness of the domestic industry and supporting policies implemented by the government.